2014
DOI: 10.1590/s1517-83822014000300045
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of the Stephanoascus ciferrii in feline otitis in Brazil

Abstract: Ear infections in cats are uncommon, especially involving yeasts. This report describes the first isolation of the Stephanoascus ciferrii, teleomorph of the Candida genus, in a case of feline otitis in Brazil. The identification and characterization of Stephanoascus ciferrii were confirmed by the Vitek2 System (BioMerieux ®).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, in 2013, C. ciferrii was found on the body surface and jaws/pharynx of Hirudo verbana leeches in Poland [127], despite no human infections having been reported in that country. In 2000, Kano et al [42] isolated in Japan the first S. ciferrii strain from a cat suffering from feline otitis followed by another case in 2014 in Brazil [128]. In 2006, Ullao et al [129] reported that Candida ciferrii was the most common yeast species isolated in bat guano in Mexico.…”
Section: S Ciferrii Complex In the One Health Perspectivementioning
confidence: 99%
“…Moreover, in 2013, C. ciferrii was found on the body surface and jaws/pharynx of Hirudo verbana leeches in Poland [127], despite no human infections having been reported in that country. In 2000, Kano et al [42] isolated in Japan the first S. ciferrii strain from a cat suffering from feline otitis followed by another case in 2014 in Brazil [128]. In 2006, Ullao et al [129] reported that Candida ciferrii was the most common yeast species isolated in bat guano in Mexico.…”
Section: S Ciferrii Complex In the One Health Perspectivementioning
confidence: 99%